Potassium monitoring in heart failure patients receiving combined therapy of captopril and furosemide - Hubby, Hubby; Suharjono, Suharjono; Djafar, Zaenab (Folia Medica Indonesiana, 2017)
In the treatment of heart failure is recommended the use of a combination of ACEI (captopril) with diuretics (furosemide), ACEI has the side effect of hyperkalemia 10-38% in hospitalized patients and 10% in outpatients, is increased in patients with renal failure and diabetes mellitus, the use diuretics occur hypokalemia 5-20% in outpatients. Hyperkalemia and hypokalemia both should be avoided in heart failure patients, because it can cause cardiac conduction disorders such as cardiac arrhythmias This study aims to monitor levels of potassium in the use of combination therapy with furosemide captopril in heart failure patients. The study was conducted using the method Prospective Observational Cross Sectional Analysis, conducted in January-May 2015 in heart failure patients male and female NYHA II-III receiving combination therapy with furosemide Captopril met the inclusion criteria were treated in the department CVCU Dr. Wahidin Sudirohusodo Makassar. Potassium levels were measured pre and post administration of the combination therapy. A total of 37 patients met the inclusion and exclusion criteria in this study, 31 male patients (83.8%) and 6 female patients (16.2%) aged between 35-80 years, during this study after administration of the combination therapy, 5 patients (13.5%) had hypokalemia (<3.5 mmol/L) and 2 patients (5.4%) experienced hyperkalemia (> 5 mmol/L) and 30 patients (81.1%) of normal potassium levels (3,5 to 5.0 mmol/L). The test results paired t test p = 0.432 (p> α;α = 0.05) showed no significant differences between potassium levels pre and post potassium levels. In conclusion, the use of a combination of captopril and furosemide therapy, the risk of hyperkalemia and hypokalemia not significant but need to be monitored levels of potassium and ECG patient.